“Wińsko upaja” and “Bagno wciąga” – on advertising slogans of Polish cities and regions - Słabczyński, Robert (Papers in Linguistics, 2020)
Place marketing in Poland is a relatively new phenomenon, and its observations focus mainly on the problems of management, psychology, sociology and visual identification. The article presents results of the research on the lexis of advertising slogans of Polish territorial units: voivodeships, counties, municipalities, communes and cities. The study presents the structure of promotional slogans, the frequency of particular parts of speech and their persuasive value. Semantic categories characteristic of the studied texts are also discussed. In order to attract people, administrative units often emphasise in their slogans the advantageous location of the place, its uniqueness as regards safety, peace, health values, clean environment, openness to different forms of human activity, modernity, development. They also refer to the local attractions, e.g. monuments, history, events which determine the specificity of the place, its strengths, competitiveness in comparison with other cities or regions. Slogans usually provide information that could help a given unit be chosen as a good place for living, investing, studying, resting, sightseeing, developing economic activity.